2019
DOI: 10.1017/jfm.2019.151
|View full text |Cite
|
Sign up to set email alerts
|

Pressure impulse theory for a slamming wave on a vertical circular cylinder

Abstract: A pressure impulse model is presented for wave impact on vertical circular cylinders. Pressure impulse is the time integral of the pressure during an impact of short time scale. The model is derived for a simplistic geometry and has relative impact height, crest length and cylinder radius as effective variables. The last parameter, the maximum angle of impact, is free and can be calibrated to yield the right force impulse. A progression of simpler pressure impulse models are derived in terms of a three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Hence, in all of our analysis, we have shown that pre-impact air cushioning has an important influence just after touchdown, but that this influence diminishes as time increases. These findings may be of significance in industries where the primary interest is in effects very close to touchdown/entry, for example, in ship-slamming or wave impacts on coastal structures, where the peak stresses are of interest [58,59]. Our analysis has shown that classical Wagner theory significantly overestimates, for example, the extent of the effective contact set and the slamming force at these times.…”
Section: Summary and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Hence, in all of our analysis, we have shown that pre-impact air cushioning has an important influence just after touchdown, but that this influence diminishes as time increases. These findings may be of significance in industries where the primary interest is in effects very close to touchdown/entry, for example, in ship-slamming or wave impacts on coastal structures, where the peak stresses are of interest [58,59]. Our analysis has shown that classical Wagner theory significantly overestimates, for example, the extent of the effective contact set and the slamming force at these times.…”
Section: Summary and Discussionmentioning
confidence: 66%
“…Note that as time increases, we converge (slowly) onto this line. The inset displays a log-log plot of the behaviour just after touchdown, with the blue-dashed line indicating the asymptotic limit (58). (Color figure online) as in (54).…”
Section: Large-time Behaviourmentioning
confidence: 99%
“…34 Because linked to the overall momentum conservation law, the pressure impulse–time integral shows a smaller variation. 35 This is proposed by Bagnold 36 first when investigating the wave impact experimentally, suggesting the pressure impulse defined as…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, breaking wave forces can be divided into two components: an impact force (or slamming force) component and a quasi-static component. The quasi-static components can be fully described using Morison's equation (FD + FM), but not the impact force (FI), as highlighted by several authors such as Goda et al (1966), Chaplin et al (1992), Wienke (2001) and Ghadirian and Bredmose (2019) [20][21][22][23]. Morison's force (FD + FM) model was extended with an additional impact force component (FI) to account for breaking wave forces, calculated using Equation (2).…”
Section: Impulsive Wave Loading Descriptionmentioning
confidence: 99%